Eksplorasi Pengalaman dan Preferensi Pengunjung terhadap Aplikasi Realitas-Virtual di Museum - Widarsyah, Redha; Wiradarmo, Aulia Ardista; Palesangi, Muliadi; Arief, Fadilah Husna (Jurnal Sosioteknologi, 2024)
In their traditional role, museums have served the purpose of preserving and educating cultural and historical artifacts. However, as time goes by, museums have grown from their traditional roles into leading-edge, interactive, experiential education platforms for visitors using the latest technological media, such as virtual reality. The study aims to explore the Indonesian museum visitors' perceptions—both positive and negative— toward VR usage in a museum and examine their expectations of an immersive VR experience, particularly related to VR games. The study employs content analysis throughan exploratory descriptive survey to address respondents' demographic background, past museum visit experience, and expectations of VR experience. Data were analyzed using thematic analysis and descriptive statistics, accompanied by a general discussion. Findings reveal the potential for utilizing VR technology at museums. Over the past ten years, there has been an expectation for museums to expand their focus from object preservation and display to visitor engagement, enabling them to create enjoyable and memorable experiences, while maintaining their mission of knowledge dissemination.